Impact of Coping Style and PTSD on Family Functioning After Deployment in Operation Desert Shield/Storm Returnees. Issue 4 (25th July 2013) - Creech, Suzannah K.; Benzer, Justin K.; Liebsack, Brittany K.; Proctor, Susan; Taft, Casey T.
<x xml:space="preserve">Abstract</x> The relationship between military combat and postdeployment family functioning difficulties has been frequently investigated in the literature, as has the relationship between types of coping and posttraumatic stress disorder (PTSD). Few studies, however, have examined these variables together, and no studies of which we are aware have examined the effect of coping on family functioning after combat exposure. This study examined coping style measured immediately after return from deployment, and PTSD symptoms and family functioning 18–24 months after return from deployment in a sample of Operation Desert Shield/Storm veterans (N = 2, 949). Structural equation models suggested that the relationships between distinct coping styles on family functioning were differentially mediated by postdeployment PTSD symptoms. Results are consistent with full mediation for avoidant coping (βdirect = −.09, p = .07; βindirect = −.17, p < .001) and partial mediation for approach coping (βdirect = .16, p < .001; βindirect = .09, p < .001). Results suggest that the strategies used to cope with a combat stress event may impact both PTSD and family functioning outcomes, and highlight the potential utility of pre‐ and postdeployment coping skills training.